2019
DOI: 10.1002/acn3.50867
|View full text |Cite|
|
Sign up to set email alerts
|

The NIH Toolbox for cognitive surveillance in Duchenne muscular dystrophy

Abstract: Objective We performed a prospective, cross‐sectional cognitive assessment in subjects with Duchenne Muscular Dystrophy (DMD) and their biological mothers. Methods Thirty subjects with out‐of‐frame mutations in the dystrophin (DMD) gene, and 25 biological mothers were evaluated using the National Institutes of Health Toolbox Cognition Battery (NIHTB‐CB). A parent completed the Behavior Rating Inventory of Executive Functioning (BRIEF), a standardized rating scale of executive functioning, for their child. Moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
3
10
0
1
Order By: Relevance
“…C‐Ms scored lower than average on executive function, as measured using the Flanker Inhibitory Control and Attention Test. On population‐normed data, the C‐Ms had lower scores on the task of attention and working memory compared with NC‐Ms 17 . Similarly, we found that C‐Ms performed worse on the attention, working memory, and executive function components.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…C‐Ms scored lower than average on executive function, as measured using the Flanker Inhibitory Control and Attention Test. On population‐normed data, the C‐Ms had lower scores on the task of attention and working memory compared with NC‐Ms 17 . Similarly, we found that C‐Ms performed worse on the attention, working memory, and executive function components.…”
Section: Discussionsupporting
confidence: 57%
“…No differences were found between C-Ms and NC-Ms on any of the other tests. working memory compared with NC-Ms. 17 Similarly, we found that C-Ms performed worse on the attention, working memory, and executive function components. However, we found these findings between the C-Ms and the control group.…”
Section: C-ms Vs Nc-mssupporting
confidence: 58%
“…Some of the neuropsychological measures used in earlier studies do not offer a continuity of measurement. In a lead study, we show that the NIH Toolbox-a scientifically robust neurobehavioral health measure-is a valid analytic tool for cognitive surveillance in DMD [68]. Last, well-powered natural history studies of cognition through a team-science approach will be extremely beneficial in DMD.…”
Section: Discussionmentioning
confidence: 93%
“…Yet the lack of reliable and robust clinical outcome measures and a well-designed natural history evaluating cognition are major impediments to progress. The use of technology-enabled tools like the NIH Toolbox ( https://www.healthmeasures.net/ explore-measurement-systems/nih-toolbox) [42] can allow for an increase in cognitive surveillance in DMD, and measures within the NIH Toolbox also has promise as a performance outcome measure for clinical trials.…”
Section: Lessons Regarding Cognition From the Dmd Natural History Stumentioning
confidence: 99%